Influence of temperature on the δ13C values and distribution of methanotroph‐related hopanoids in Sphagnum‐dominated peat bogs. Issue 4 (16th March 2020) - van Winden, Julia F.; Talbot, Helen M.; Reichart, Gert‐Jan; McNamara, Niall P.; Benthien, Albert; Sinninghe Damsté, Jaap S.
Abstract: Methane emissions from peat bogs are mitigated by methanotrophs, which live in symbiosis with peat moss (e.g. Sphagnum ). Here, we investigate the influence of temperature and resultant changes in methane fluxes on Sphagnum and methanotroph‐related biomarkers, evaluating their potential as proxies in ancient bogs. A pulse‐chase experiment using 13 C‐labelled methane in the field clearly showed label uptake in diploptene, a biomarker for methanotrophs, demonstrating in situ methanotrophic activity in Sphagnum under natural conditions. Peat cores containing live Sphagnum were incubated at 5, 10, 15, 20 and 25°C for two months, causing differences in net methane fluxes. The natural δ 13 C values of diploptene extracted from Sphagnum showed a strong correlation with temperature and methane production. The δ 13 C values ranged from −34‰ at 5°C to −41‰ at 25°C . These results are best explained by enhanced expression of the methanotrophic enzymatic isotope effect at higher methane concentrations. Hence, δ 13 C values of diploptene, or its diagenetic products, potentially provide a useful tool to assess methanotrophic activity in past environments. Increased methane fluxes towards Sphagnum did not affect δ 13 C values of bulk Sphagnum and its specific marker, the C23 n ‐alkane. The concentration of methanotroph‐specific bacteriohopanepolyols (BHPs), aminobacteriohopanetetrol (aminotetrol, characteristic for type II and to a lesser extent type I methanotrophs) and aminobacteriohopanepentol (aminopentol, a marker for type I methanotrophs) showed a non‐linear response to increased methane fluxes, with relatively high abundances at 25°C compared to those at 20°C or below. Aminotetrol was more abundant than aminopentol, in contrast to similar abundances of aminotetrol and aminopentol in fresh Sphagnum . This probably indicates that type II methanotrophs became prevalent under the experimental conditions relative to type I methanotrophs. Even though BHP concentrations may not directly reflect bacterial activity, they may provide insight into the presence of different types of methanotrophs.